2021
DOI: 10.31413/nativa.v9i2.12047
|View full text |Cite
|
Sign up to set email alerts
|

Impactos Técnico-Econômicos Da Adubação De Pastos

Abstract: A criação de bovinos no Brasil ocorre, prioritariamente, em pastagens e, neste contexto, a adubação do pasto é uma importante estratégia de aumento na eficiência produtiva. Diante disso, objetivou-se, com esta revisão, descrever os impactos técnicos da adubação no desenvolvimento de gramíneas tropicais. A calagem é uma prática importante na disponibilidade dos nutrientes e, novos estudos visam demonstrar que o intervalo entre a incorporação do calcário e a semeadura tem maior dependência da umidade do solo e q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…They found that regardless of the combination of single superphosphate and natural phosphate, the mean values did not differ significantly, and all treatments had higher mean values than the control. Cabral et al (2021) observed that in the absence of P, grasses of the genus Panicum implanted in an Oxisol with low P content experienced a reduction in production of approximately 98.5%, highlighting the impact of this nutrient on pasture formation for this genus. that from the second cut onwards, the less soluble sources such as NP and Djebel-Onk reactive natural phosphate-based fertilizers showed better performance.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…They found that regardless of the combination of single superphosphate and natural phosphate, the mean values did not differ significantly, and all treatments had higher mean values than the control. Cabral et al (2021) observed that in the absence of P, grasses of the genus Panicum implanted in an Oxisol with low P content experienced a reduction in production of approximately 98.5%, highlighting the impact of this nutrient on pasture formation for this genus. that from the second cut onwards, the less soluble sources such as NP and Djebel-Onk reactive natural phosphate-based fertilizers showed better performance.…”
Section: Resultsmentioning
confidence: 95%
“…Brazil has the second largest herd globally, with 213.68 million head, representing 13% of the world herd and contributing 8.5% of the country's GDP (Gross Domestic Product) (Associação Brasileira das Indústrias Exportadoras de Carnes [ABIEC], 2020). The majority of this herd relies on pastures as their primary food source, under extensive grazing systems with limited management control and without nutrient replenishment (Cabral et al, 2021). Consequently, productivity remains low, as indicated by an average animal stocking of only 1.06 AU ha-1, hindering the sector from reaching higher levels (ABIEC, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No país, o setor agropecuário ocupa atualmente uma área de 350 milhões de hectares, dos quais, aproximadamente 172 milhões são destinados a pastagens, estando a pecuária extensiva como responsável por 93% do rebanho bovino (IBGE, 2023). Este segmento produtivo representa cerca de 30% do PIB (Produto Interno Bruto) do agronegócio brasileiro, tendo como principal fonte alimentar as plantas forrageiras (FARIAS et al, 2019;TERRA et al, 2019;CABRAL et al, 2021).…”
Section: Introductionunclassified
“…A adubação do pasto é uma importante estratégia para o aumento na eficiência produtiva (CABRAL et al, 2021), principalmente em Latossolos, que são solos de elevada acidez, baixo teor de fósforo e bases, o que requer reposição de nutrientes para manutenção do potencial produtivo (ALMEIDA et al, 2021). Assim, a adubação é uma prática muito relevante para a manutenção produtiva das pastagens, entretanto, o uso racional de fertilizantes exige a identificação dos nutrientes prioritários para implantação e manutenção das mesmas (CABRAL et al, 2021).…”
Section: Introductionunclassified